Hollow microspheres formed by nanograins of Cr1.8Ti0.2O3+z synthesized by ultrasonic spray pyrolysis for acetone detection - Carol Coronel, Francisco Jonás; Tobia, Dina; Lima, Enio Junior; Sanchez, Rodolfo Daniel; Saleta, Martin Eduardo (Pergamon-Elsevier Science Ltd, 2023)
Fil: Carol Coronel, Francisco Jonás. Comisión Nacional de Energía Atómica. Gerencia del Área de Energía Nuclear. Instituto Balseiro; Argentina. Universidad Nacional de Santiago del Estero; Argentina